EFEKTIFITAS PEMUNGUTAN PAJAK BUMI DAN BANGUNAN PERDESAAN PERKOTAAN (PBB-P2) DENGAN PENDEKATAN STRATEGY SWOT ANALYSIS DI KABUPATEN ENREKANG - Mustafa Hasbar; Agung Wijaya (AkMen JURNAL ILMIAH, 2017)
This study aimed to analyze the effectiveness of the implementation of land and building tax collection Rural Urban (PBB-P2) and to determine the effectiveness of the strategy of land and building tax collection Rural Urban (UN-PD) in Enrekang. The population sample as many as 663 people and 86 people. Data collection techniques are interviews, questionnaires and studies commentary. Data analysis techniques using descriptive and SWOT analysis. The results showed that the effectiveness appraisal recapitulation collection and Building Tax (PBB-P2) in Enrekang show category ineffective with spots weighting of 1560. The identification of internal factors that force (strenght) obtained a value of 2.5 and weakness (weakness) value 3.0. While external factors to keategori chance (opportunity) obtained grades 3.3 and threat categories (threath) with a value of 3.0. If seen from the results of the identification of internal factors and eksternsl the positions collection strategy effectiveness and Building Tax Rural and Urban Areas (PBBP2) in Enrekang shows that for the time being the most appropriate strategy is to do with Aggressive Strategy.